Psychology of the stock market - Selden, G. C. (George Charles), 1870- (Salt Lake City, UT : Project Gutenberg, 2025)
"Psychology of the Stock Market" by G. C. Selden is a scientific publication written in the early 20th century. The book explores the psychological factors that influence stock market behavior, arguing that investor psychology significantly impacts price movements. Through careful analysis and practical insights, Selden aims to bridge the gap between psychological theories and their application in trading and investment decisions. In this book, G. C. Selden examines the complex interplay between the human psyche and stock market fluctuations. He discusses concepts such as the speculative cycle, inverted reasoning, market panic, and the mental attitudes of traders. Selden illustrates how public sentiment can lead to irrational market behaviors, such as excessive optimism during booms and unwarranted fear during panics. By dissecting these psychological aspects, Selden provides valuable strategies for investors and traders to improve their decision-making processes, emphasizing the importance of understanding market psychology over solely relying on technical and fundamental analysis. (This is an automatically generated summary.)
Release date is 2025-03-09
Bob Taylor, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Investments -- Psychological aspects; Speculation